2014
DOI: 10.5826/dpc.0401a09
|View full text |Cite
|
Sign up to set email alerts
|

Prediction without Pigment: a decision algorithm for non-pigmented skin malignancy

Abstract: While there are several published comprehensive stepwise algorithmic methods for diagnosing pigmented skin malignancy, only limited material has been published for the stepwise assessment of non-pigmented lesions. We present a method based on pattern analysis, with a stepwise assessment, first, for ulceration, second, for white clues (defined as white lines, or in the case of a raised lesion any of the keratin clues: dermatoscopic white circles, dermatoscopic white structureless areas or surface keratin), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 21 publications
(24 reference statements)
1
26
0
3
Order By: Relevance
“…Although the majority of melanomas in our study revealed a polymorphic pattern, we found that some types of vessels more commonly co‐occur. The co‐occurrence of dotted and linear straight vessels as an indicator for melanoma of intermediate thickness is very well established, and our results again confirm this observation . A clue to differentiate between benign and malignant tumours showing dotted vessels lies particularly in the arrangement, as, for example, dots in melanocytic skin lesions commonly appear regularly distributed.…”
Section: Frequencies Of Different Vascular Patterns In Relation To Mesupporting
confidence: 86%
See 1 more Smart Citation
“…Although the majority of melanomas in our study revealed a polymorphic pattern, we found that some types of vessels more commonly co‐occur. The co‐occurrence of dotted and linear straight vessels as an indicator for melanoma of intermediate thickness is very well established, and our results again confirm this observation . A clue to differentiate between benign and malignant tumours showing dotted vessels lies particularly in the arrangement, as, for example, dots in melanocytic skin lesions commonly appear regularly distributed.…”
Section: Frequencies Of Different Vascular Patterns In Relation To Mesupporting
confidence: 86%
“…D ear E ditor , In nonpigmented skin tumours the diagnosis is based mainly on the evaluation of the vascular morphology and vessels’ distribution dermoscopically . However, to date, no study has formally correlated the prevailing vascular morphology with the Breslow thickness of the melanoma and the amount of pigmentation.…”
Section: Frequencies Of Different Vascular Patterns In Relation To Mementioning
confidence: 99%
“…These elements are part of a group called "white lines", and are among those only visible with polarized light, the "bright structures" [9].…”
Section: Commentsmentioning
confidence: 99%
“…Linear curved vessels (“comma vessels”), typical for dermal nevi (“Unna nevi”), have been reported by Menzies et al as a negative predictive factor for melanoma . According to a recent suggestion by Rosendahl et al it is important to differentiate between flat and raised amelanotic melanoma . Flat amelanotic melanomas are typified by polymorphic vessels that include a pattern of vessels as dots.…”
Section: Dermatoscopic Evaluation Of Vascular Structures In Ahmmentioning
confidence: 99%
“…Nodular amelanotic melanoma should be suspected in any non‐pigmented nodule that lacks a specific distribution of vascular structures and when a specific benign diagnosis cannot be made with confidence. They also pointed out the importance of other clues such as ulceration and white structures .…”
Section: Dermatoscopic Evaluation Of Vascular Structures In Ahmmentioning
confidence: 99%